A simulation study to evaluate contamination during reuse of N95 respirators and effectiveness of interventions to reduce contamination. (10th June 2022) - Li, Daniel F.; Alhmidi, Heba; Scott, Jacob G.; Charnas, Ian C.; Pearlmutter, Basya; Silva, Sandra Y.; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: Objective: To assess the potential for contamination of personnel, patients, and the environment during use of contaminated N95 respirators and to compare the effectiveness of interventions to reduce contamination. Design: Simulation study of patient care interactions using N95 respirators contaminated with a higher and lower inocula of the benign virus bacteriophage MS2. Methods: In total, 12 healthcare personnel performed 3 standardized examinations of mannequins including (1) control with suboptimal respirator handling technique, (2) improved technique with glove change after each N95 contact, and (3) control with 1-minute ultraviolet-C light (UV-C) treatment prior to donning. The order of the examinations was randomized within each subject. The frequencies of contamination were compared among groups. Observations and simulations with fluorescent lotion were used to assess routes of transfer leading to contamination. Results: With suboptimal respirator handling technique, bacteriophage MS2 was frequently transferred to the participants, mannequin, and environmental surfaces and fomites. Improved technique resulted in significantly reduced transfer of MS2 in the higher inoculum simulations ( P < .01), whereas UV-C treatment reduced transfer in both the higher- and lower-inoculum simulations ( P < .01). Observations and simulations with fluorescent lotion demonstrated multiple potential routes of transfer to participants, mannequin, and surfaces, including both direct contact with the contaminated respirator and indirect contact via contaminated gloves. Conclusion: Reuse of contaminated N95 respirators can result in contamination of personnel and the environment even when correct technique is used. Decontamination technologies, such as UV-C, could reduce the risk for transmission.